The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13203-015-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of synthesis of cyclopentanol from cyclopentene and comparison with experimental data

Abstract: Cyclopentanol is a very important chemical intermediate, which has been widely used in the chemical industry, and could be prepared from cyclopentene by two steps: an initial addition-esterification reaction of cyclopentene with acetic acid and the subsequent transesterification reaction with methanol. However, so far, no direct theoretical or experimental work has been reported on this process. In this work, we have carried out the thermodynamic calculation of the indirect process and also validated the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The feasibility of this methodology had been confirmed by Steyer and co-workers, indicating the advantages of high reaction selectivity, low pollution and corrosion, and mild reaction conditions. Moreover, it is worth noting that the esterification of cyclohexene with carboxylate acid is the determining step in the whole indirect hydration . That is to say, improving the rate of the first step of indirect hydration can effectively increase the yield of target product alcohol, in which the activity of catalysts employed is particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of this methodology had been confirmed by Steyer and co-workers, indicating the advantages of high reaction selectivity, low pollution and corrosion, and mild reaction conditions. Moreover, it is worth noting that the esterification of cyclohexene with carboxylate acid is the determining step in the whole indirect hydration . That is to say, improving the rate of the first step of indirect hydration can effectively increase the yield of target product alcohol, in which the activity of catalysts employed is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is worth noting that the esterification of cyclohexene with carboxylate acid is the determining step in the whole indirect hydration. 10 That is to say, improving the rate of the first step of indirect hydration can effectively increase the yield of target product alcohol, in which the activity of catalysts employed is particularly important. However, the conventional solid acid catalyst ion-exchange resins Indion-130 and Amberlyst-15 were found to induce <50% conversions of cyclohexene in the esterification of cyclohexene and formic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This type of membrane has promising application possibilities. 84 The inorganic materials that are frequently utilized for the preparation of composite membranes include zeolite molecular sieves, 85 metal-organic frameworks 86 and carbon nanotubes. 87 Jiang et al 88 introduced a zeolite thin layer into a PSF/Matrimid hollow ber membrane and found that the selectivity for CO 2 in a CO 2 /CH 4 mixed system was enhanced by 50%.…”
Section: Composite Membranesmentioning
confidence: 99%
“…Using a thermodynamic analysis of chemical equilibrium is helpful to understand the significance of each reaction. [42][43][44] The group contribution method proposed by Yoneda et al is a widely-used approach to predict the thermodynamic properties for chemical equilibrium analysis. [45][46][47][48] Here we have applied a combination of experimental and theoretical investigations: analyzing the reaction routes by experiments and identifying the considerable side reactions by thermodynamics calculation, which is an effective and low-cost way to determine the routes for a complex reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…Although the analysis and testing methods could accurately quantify all the components and help identify the significance of each side reaction, they are costly and time‐consuming, especially in case of many complex components. Using a thermodynamic analysis of chemical equilibrium is helpful to understand the significance of each reaction 42–44 . The group contribution method proposed by Yoneda et al .…”
Section: Introductionmentioning
confidence: 99%